Redescription and affinities of Hulsanpes perlei (Dinosauria, Theropoda) from the Upper Cretaceous of Mongolia - Cau,Andrea; Madzia,Daniel (PeerJ, 2018)
Hulsanpes perlei is an enigmatic theropod dinosaur from the Baruungoyot Formation (?mid- to upper Campanian, Upper Cretaceous) of Mongolia. It was discovered in 1970, during the third Polish-Mongolian paleontological expedition to the Nemegt Basin. The taxon is known based on a partial braincase and an incomplete right hindlimb. However, the braincase fragment has never been described nor illustrated. We redescribe all elements that form the holotype of Hulsanpes and discuss the affinities of this taxon. The braincase fragment is interpreted as belonging to the inner ear region, and includes the floccular recess and part of the labyrinth. Hulsanpes perlei is confirmed as a valid taxon, diagnosed by a unique combination of metatarsal characters, including two autapomorphies. Historically, it represents the oldest record of the recently-established clade Halszkaraptorinae. Our findings identify subcursorial adaptations for Hulsanpes, shared with Mahakala, and differentiating them from Halszkaraptor. As such, appendicular disparity in the potentially sympatric halszkaraptorines suggest a reduced ecological overlap among these taxa, which may explain the co-occurrence of multiple species of this clade during the latest Cretaceous in what is now the Nemegt Basin.
Keywords: Cretaceous; Halszkaraptorinae; Dromaeosauridae; Hulsanpes perlei; Mongolia; Theropoda